2013
DOI: 10.1002/jbmr.2155
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity in the Response of the Proximal Femur to Two Lower-Body Resistance Exercise Regimens

Abstract: Understanding the skeletal effects of resistance exercise involves delineating the spatially heterogeneous response of bone to load distributions from different muscle contractions. Bone mineral density (BMD) analyses may obscure these patterns by averaging data from tissues with variable mechano-response. To assess the proximal femoral response to resistance exercise, we acquired pre- and post-training quantitative computed tomography (QCT) images in 22 subjects (25-55 years, 9 males, 13 females) performing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 27 publications
6
47
1
2
Order By: Relevance
“…Lang et al [139] and Loehr et al [140] found statistically significant increases in the bone mineral density (BMD) of lumbar vertebral bodies (L1-L2) of between 7 and 12.3 % after only 4 months of DUP with 6-10 RM [139] and 70-80 % 1 RM [140]. The subjects performed parallel squats and dead lifts.…”
Section: Progression Rates Of Strength and Speedstrength Characteristmentioning
confidence: 95%
“…Lang et al [139] and Loehr et al [140] found statistically significant increases in the bone mineral density (BMD) of lumbar vertebral bodies (L1-L2) of between 7 and 12.3 % after only 4 months of DUP with 6-10 RM [139] and 70-80 % 1 RM [140]. The subjects performed parallel squats and dead lifts.…”
Section: Progression Rates Of Strength and Speedstrength Characteristmentioning
confidence: 95%
“…Recently, there have been contrary reports to the effect of alendronate on bone‐formation rates . There have also been variable reports of resistance exercise to be a countermeasure to disuse‐induced bone loss . Leblanc and colleagues utilized a newer advanced resistance‐exercise device with bisphosphonates to demonstrate the protection of bone during spaceflight with increases from BMD scans, elevated measures of bone‐resorption markers, and urinary excretion of calcium .…”
Section: Introductionmentioning
confidence: 99%
“…It also raises the question as to whether physical activity–induced bone adaptation occurs at this location. Initial studies using three‐dimensional (3D) imaging techniques have explored adaptation of the superior femoral neck to physical activity, but the data remain inconclusive . Some studies suggested physical activity may positively influence the superior femoral neck, whereas others reported no effect …”
Section: Introductionmentioning
confidence: 99%